(untitled) (Research, Society and Development, 2021)
Corn is part of the Brazilian food base. The objective of this study was to analyze the attributes that best represent the wet mass of the corn cob, through the trail analysis, allowing to establish correlations between these variables, which are indicative of corn productivity and quality. This study was carried out in the municipality of Parauapebas-PA, on the premises of the experimental area of the Technological Center for Family Agriculture (CETAF). The attributes of the corn cob were: wet cob mass (MAU), wet cob husk (CAU), wet cob (SAU), wet cob grain (GRU), dry cob mass (MAS), dry grain masses (GRS), dry cob (SAS) and dry ear husk (CAS). Results showed by the Pierson correlation that that wet ear bark and wet ear mass showed a high positive correlation. As a conclusion, the trail analysis made it possible to verify that, directly, the attributes wet humid and wet grains of the ear are the attributes that best serve to evaluate the wet mass of the ear of corn. Indirectly, we observed via trail analysis that the wet peel has a positive correlation with dry peel and dry mass of the ear and negative with wet sabote and dry grains of the ear.